Impact of aging on the frequency, phenotype, and function of CD4+ T cells in the human female reproductive tract - Shen, Zheng; vom Steeg, Landon G.; Patel, Mickey V.; Rodriguez-Garcia, Marta; Wira, Charles R. (Frontiers in Immunology, 2024)
Since CD4+ T cells are essential for regulating adaptive immune responses and for long lasting mucosal protection, changes in CD4+ T cell numbers and function are likely to affect protective immunity. What remains unclear is whether CD4+ T cell composition and function in the female reproductive tract (FRT) changes as women age. Here we investigated the changes in the composition and function of CD4+ T cells in the endometrium (EM), endocervix (CX), and ectocervix (ECX) with aging. We observed a significant decrease in both the total number and percentage of CD4+ T cells in the EM with increasing age, particularly in the years following menopause. CD4+ T cells within the FRT predominantly expressed CD69. The proportion of CD69+CD4+ T cells increased significantly with increasing age in the EM, CX and ECX. The composition of T helper cell subsets within the EM CD4+ T cell population also showed age-related changes. Specifically, there was a significant increase in the proportion of Th1 cells and a significant decrease in Th17 and Treg cells with increasing age. Furthermore, the production of IFNγ by CD4+ T cells in the EM, CX, and ECX significantly decreased with increasing age upon activation. Our findings highlight the complex changes occurring in CD4+ T cell frequency, phenotype, and function within the FRT as women age. Understanding these age-related immune changes in the FRT is crucial for enhancing our knowledge of reproductive health and immune responses in women.